1995
DOI: 10.1007/bf00576259
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of insulin stores in Langerhans islets by combined immunohistochemistry and computerized microspectrophotometric analysis

Abstract: Histology, size, and insulin content of Langerhans islets from normal and recent experimental hyperthyroid (REH) dogs were studied. Insulin localization in the islets was revealed by immunohistochemistry, and the remaining two variables were analyzed by computerized microspectrophotometry according to an original technique described here. Observed under the light microscope, the REH dog pancreas section shows larger than normal islets whose scarce beta-granules are mainly located near B-cell borders and groupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Renauld and co‐workers showed that the administration of thyroid hormone to normal dogs for 10 days produced a significant decrease in islet insulin content54, and that experimental hyperthyroidism significantly impaired blood sugar, serum insulin and serum non‐sterified fatty acid responses to glucose55.…”
Section: Basic Researchmentioning
confidence: 99%
“…Renauld and co‐workers showed that the administration of thyroid hormone to normal dogs for 10 days produced a significant decrease in islet insulin content54, and that experimental hyperthyroidism significantly impaired blood sugar, serum insulin and serum non‐sterified fatty acid responses to glucose55.…”
Section: Basic Researchmentioning
confidence: 99%